The effect of steady torsion on fatigue crack growth under rotating bending loading on aluminium alloy 7075-T6 - M. da Fonte; L. Reis; M. de Freitas (Fracture and Structural Integrity)
Axles and shafts are of prime importance concerning safety in the transportation industry and railway in particular. Design rules for axles and shafts are mainly based on endurance curves for the material used according to the established standards and procedures. Recently, the knowledge of fatigue crack growth under typical loading conditions of axles and shafts with rotating bending and steady torsion is being object of research and industrial studies in order to apply damage tolerance concepts, mainly for maintenance purposes. The effect of a steady torsion on fatigue crack growth under rotating bending is focused in this paper. While axles and shafts in the transportation industry are traditionally designed on steels, the need for weight reduction due to fuel economy and eco-design constraints, lightweight materials must be considered for these applications. In this study, fatigue crack growth on rotating bending axles and shafts with or without an applied steady torsion is presented. Fracture mechanics approaches are used to analyze the results based on Stress Intensity Factors developed for bending and torsion in shafts and show fatigue crack growth retardation when steady torsion is applied. Fractographic observations using SEM are presented and helped to explain the fatigue crack growth retardation observed when steady torsion is applied to rotating bending. Results are compared for the same loading conditions on steels and relevant differences on fatigue crack growth are commented.